P181 CARDIAC PROTECTION BY PIRFENIDONE AFTER MYOCARDIAL INFARCTION: A BIOINFORMATIC ANALYSIS. (18th May 2022) - Aimo, A; Iborra–Egea, O; Martini, N; Galvez–monton, C; Burchielli, S; Panichella, G; Passino, C; Emdin, M; Bayes–Genis, A
Abstract: Purpose: Left ventricular (LV) remodeling after myocardial infarction (MI) is promoted by an intense fibrotic response, which could be targeted by an anti–fibrotic drug such as pirfenidone. Methods: We explored the relationship between protein modulation by pirfenidone and post–MI remodeling, based on publicly available molecular information and transcriptomic data from a swine model of MI. We also compared the effects of pirfenidone and angiotensin–converting enzyme inhibitors/angiotensin receptor blockers (ACEi/ARB), mineralocorticoid receptor blockers (MRA) and beta–blockers. Results: We identified 6 causative motives of post–MI remodeling (cardiomyocyte cell death, impaired myocyte contractility, extracellular matrix remodeling and fibrosis, hypertrophy, renin–angiotensin–aldosterone system activation, and inflammation), 4 pirfenidone targets and 21 bioflags (indirect effectors). When considering both targets and bioflags, pirfenidone showed a broad relationship encompassing all 6 motives. p38γ–MAPK12 blockade inhibits cardiomyocyte apoptosis, cardiomyocyte hypertrophy and inflammation. Furthermore, pirfenidone can modulate extracellular matrix remodeling and cardiac fibrosis by targeting the TGFβ1–SMAD2/3 pathway and other effector proteins such as matrix metalloproteases 2 and 14, PDGFA/B, and IGF1, which promote myocardial fibrosis, cardiomyocyte hypertrophy and impaired contractility. All the gold standard drugs were found to be important for specific clinical motives, but pirfenidone had a more widespread action on the molecular pathways active in the post–MI setting. Conclusion: A bioinformatic approach allowed to identify several possible mechanisms of action of pirfenidone with beneficial effects in the post–MI LV remodeling, and suggests additional effects over guideline–recommended therapies. These findings support clinical studies evaluating the beneficial effects of pirfenidone in patients with MI.